Qualitative Identification of Dimensions and Components of Good Governance in Relation to Organizational Intimacy and Organizational Development at Mazandaran University of Medical Sciences - Rezazadeh Taloukolaei, Fatemeh; Zameni, Farshideh; Enayati , Taraneh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The present research aimed to qualitatively identify the dimensions and components of good governance in relation to organizational intimacy and organizational development at Mazandaran University of Medical Sciences. Method: This study, based on its objectives, is an applied-developmental study that utilized qualitative research methods. Additionally, to gather information, library study and semi-structured interviews were employed. Initially, for the theoretical study related to the research objective and to review the literature and background of the topic, information from relevant specialized books and articles addressing the relationship between organizational intimacy and good governance with organizational development was used. Subsequently, to identify the dimensions of the research variables, semi-structured interviews with experts were conducted. Then, the qualitative method of thematic analysis was applied to analyze the data obtained from the interviews. The population of this research included the managers of Mazandaran University of Medical Sciences and academic experts (with research and publications in this field) who were selected through purposive sampling and included 10 interviewees determined by theoretical saturation. Findings: A total of 344 primary codes were extracted from the interview texts. Through coding these concepts, 59 sub-themes were identified and by classifying these themes into similar categories, 11 main themes were derived. Conclusion: The main themes included good governance, value-orientation, capacity building, transparency, accountability, emotional closeness, organizational climate, organizational intimacy, non-financial performance, financial performance, and organizational development. In this context, there is a need for access to high-ranking managers and officials, and indeed for servant leadership among university administrators. Also, with the honesty of university managers, objectives related to skill development and knowledge updating can be achieved. In addition to the aforementioned issues, attention to the quantitative and qualitative growth and development of employees is also considered a part of good governance that should be increasingly focused on by relevant managers.